Repetitively pulsed X-ray laser operating on the 3p - 3s transition of the Ne-like argon in a capillary discharge - Rocca, Jorge J., author; Vinogradov, A. V., author; Kvantovaya Elektronika and Turpion Ltd., publisher (Colorado State University. Libraries, 2003)
The paper is devoted to a 469-Å X-ray laser excited by a fast capillary discharge in argon. The basic characteristics of the active medium and laser beam are presented. Applications of the laser in the studies of plasmas with densities of up to 1020 cm-3, in interferometry, reflectometry, for analysis of materials, etc. are described. A brief historical review is presented and the current state of the art in the development of laboratory X-ray lasers is considered.
Keywords: capillary discharge laser; X-ray lasers